Psychosocial Impact of Lockdown Due to Novel Corona Virus COVID-19 among Medical Undergraduate Students - Rupali Sarode; Prakash Mohite; Sourya Acharya; Samarth Shukla; Shashank Gotarkar (Research Highlights in Disease and Health Research Vol. 4, 2023)
The outbreak of Novel Corona Virus Disease (COVID-19) which started in the late 2019, in Wuhan in Hubei province of China because of its high infectivity and fatality rate, had a widespread psychosocial impact on people. This was evidenced as mass hysteria, economic burden and financial losses. Mass fear of COVID-19, termed as “Coronaphobia”, had generated a plethora of psychiatric manifestations across different strata of the society. As a result, this study was conducted to define the psychosocial impact of COVID-19 on Medical graduates with the goal of assessing the reasons for breaking the lockdown and the level of psychosocial impact of lockdown on Medical graduates during the COVID-19 lockdown period. A cross-sectional prospective study was conducted on 285 MBBS students from first to final year. Data was collected using the Validated Psychosocial Impact Scale. The outcomes demonstrated the severity of the negative effects of lockdown on the medical college students. 18.60% of students responded normally to the COVID 19 pandemic lockdown situation. Students in 47.72% showed a possible negative effect from lockdown. No student was found to be in the range of a severe negative impact of lockdown, while 29.12 students had a mild negative impact and 4.56% had a moderate negative impact.